2021
DOI: 10.2147/cmar.s309226
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Orthotopic Genital Cancer Induced by Subcutaneous Administration of Human Papillomavirus Peptide Vaccine with CpG Oligodeoxynucleotides as an Adjuvant in Mice

Abstract: Persistent high-risk human papillomavirus (HPV) infection is the most common cause of cervical cancer and its precursor lesions. Although prophylactic HPV vaccines have been applied in the general population for the prevention of HPV infections, no licensed therapeutic HPV vaccine is currently available to treat preexisting HPV infections or HPVassociated diseases, including cervical cancer. Materials and Methods: The most common murine cervical cancer model used for the evaluation of the efficacy of a therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…It has been reported that exosome‐mediated transfer of circHIPK3 acted as a ceRNA to promote trastuzumab resistance in breast cancer (Zhang et al, 2021). Moreover, Ni et al reported that circHIPK3 regulated Paclitaxel resistance via the miR‐1286/HK2 axis in breast cancer (Wang et al, 2021). In addition, circHIPK3 could facilitate Temozolomide resistance through activation of the PI3K/AKT pathway or the miR‐421/ZIC5 Axis in glioma (Han et al, 2021; Yin & Cui, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that exosome‐mediated transfer of circHIPK3 acted as a ceRNA to promote trastuzumab resistance in breast cancer (Zhang et al, 2021). Moreover, Ni et al reported that circHIPK3 regulated Paclitaxel resistance via the miR‐1286/HK2 axis in breast cancer (Wang et al, 2021). In addition, circHIPK3 could facilitate Temozolomide resistance through activation of the PI3K/AKT pathway or the miR‐421/ZIC5 Axis in glioma (Han et al, 2021; Yin & Cui, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…reported that circHIPK3 regulated Paclitaxel resistance via the miR-1286/HK2 axis in breast cancer (Wang et al, 2021). In addition, circHIPK3 could facilitate Temozolomide resistance through activation of the PI3K/AKT pathway or the miR-421/ZIC5 Axis in glioma (Han et al, 2021;Yin & Cui, 2021).…”
Section: Serum Exosomal Circhipk3 May Be a Potential Indicator For Ev...mentioning
confidence: 97%
“…A limitation of peptide‐based vaccines is their suboptimal immunogenicity, prompting the requirement for adjuvants to augment their efficacy. Adjuvants such as CpG oligodeoxynucleotides, 313 , 314 cobalt‐porphyrin‐phospholipid, 315 and manganese (Mn4+)‐doped silica nanoparticles (Mn4+‐SNPs) 316 have been found to enhance immune responses.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%